Landslide Susceptibility Mapping using Geographic Information System (GIS) and Remote Sensing Data in North Luwu, South Sulawesi Province, Indonesia - Chalik, Citra Aulian; Wakila, Muhamad Hardin; Jafar, Nurliah; Nurhawaisyah, Sitti Ratmi; Firdaus; Heriansyah, Andi Fahdli (Journal of Geology and Exploration, 2023)
Climate, topography, and rock conditions in Indonesia are relatively diverse, both physical and chemical, these conditions can cause adverse consequences such as floods, landslides, forest fires, and droughts. The Information from Volcanology and Geological Disaster Mitigation on Monday, July 13, 2020, flash floods and flow of debris due to landslides have occurred in Masamba and Baebunta, North Luwu, South Sulawesi Province. The purpose of this paper is to map the distribution of landslide susceptibility area using remote sensing and GIS data. The Method used to analyze the landslide susceptibility estimation model refers to the Indonesian Center for Agricultural Land Resources Research and Development (ICALRD). The parameters used in this model are rainfall, soil type, rock type, slope, land use, and land movement. The ICALRD Landslide Susceptibility Estimation Model in study area shows that there are three classes of landslide susceptibility, such as low, medium, and high susceptibilities. There are six subdistricts which are in medium to high landslide susceptibility, and the others are low to medium landslide susceptibility. The locations of landslides and flash floods that occurred in Masamba and Baebunta indicate areas with medium to high landslide susceptibility.